Demand for Economics Journals: A Cross Section Analysis - Odagiri, Hiroyuki (The Review of Economics and Statistics, 1977)
Which economics journal is most prestigious? and/or Which journal is most popular? are, for economists, some of the most hotly debated questions of coffee break discussions. In addition, which journal to subscribe to might be one of the most important decisions an economist makes. On the other hand, the proposition that the demand for a commodity depends on its price and its quality, among other things, is one of the (few!) propositions that every economist agrees with. In view of these facts, it seems rather curious to the present author that no one, so far as he knows, has ever estimated the demand function for economics journals. The purpose of this paper is to try to fill this gap and to estimate the demand function for economics journals by means of a cross section analysis. The result of the estimation will be presented in section III. Before that, however, the model used in our study will be explained.